PENGARUH STRUKTUR KEUANGAN TERHADAP KEMAMPUAN PEROLEHAN LABA DALAM LQ 45 - Ramadhianti, Arina; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test empirically and to analysis the influence of assets structure, firm size and capital structure to the profit gain ability (ROA) on the company which is incorporated in the LQ 45 Index in Indonesia Stock Exchange in 2009-2012 periods. Multiple linear regressions are used in this research with the samples are 19 companies which are incorporated in LQ 45 index in Indonesia Stock Exchange in 2009-2012 periods. The secondary data has been obtained from Indonesia Stock Exchange Corner of STIESIA Surabaya. The SPSS program 2.0 versions are used as analysis technique. The result that has been obtained based on the goodness of fit test shows that the regressions model is feasible to be use in order to predict the influence of assets structure, firm size and capital structure to the dependent variable that is profit gain ability (ROA) on the companies which are incorporated in the LQ 45 in Indonesia Stock Exchange in 2009-2012 periods. The determination coefficient test (R2) has large contribution since the result of output of SPSS 20 is 0.495 or 49.5% whereas the result of multiple correlation coefficient (R) is 0.566 or 56.6% and its relation is quite firm. Hypothesis test partially generates the result of firm size and capital structure variables have positive influence to the profit gain ability (ROA) on the companies which are incorporated in Indonesia Stock Exchange in 2009-2012 periods whereas the assets structure variable does not have any influence to the profit gain ability (ROA).Keywords: Assets Structure (TANG), Firm Size, and Capital Structure (DER) and Return on Assets (ROA).